Creating the Universe: Depictions of the Cosmos in Himalayan Buddhism, by Eric Huntington - Samuel, Geoffrey (Religions of South Asia, 2023)
Creating the Universe: Depictions of the Cosmos in Himalayan Buddhism, by Eric Huntington. Seattle: University of Washington Press, 2019. xx + 283 pp., $65 (hb). ISBN: 9780295744063.